Enhancing the Capability of Central Finance Agencies - Allen, Richard; Grigoli, Francesco (World Bank, Washington, DC, 2012)
A well-organized and effective finance ministry and its associated central finance agencies (CFAs) are essential to good fiscal outcomes. Recent studies of CFAs in selected low-income countries demonstrate that their organizational structure varies widely and that decision making on public finance is strongly influenced by political economy factors. This note presents some common themes arising from the case studies and provides some descriptive evidence about the organizational structure of the CFAs. This note also includes evidence of a 'U-curve' pattern in the development of the organizational structure of CFAs over the long term. It confirms that political economy analysis, though difficult to apply in practice, is highly relevant in the development of reform strategies for strengthening CFAs and public financial management systems.